Deployment Plan of Wireless Distribution System of ASIST Intranet Network Infrastructure - Excel Philip B. Guidang (JPAIR Institutional Research Journal)
Corporate giants have long recognized the importance of intranet in doing business. It is often implemented using conventional structured cabling.  It increases productivity and produces higher Return on Investment (ROI). The study was conducted to develop Abra State Institute of Sciences and Technology (ASIST) Intranet Network Plan.  It employed the descriptive and applied methods of research. A pre-validated research survey questionnaire adopted from the E-Government Fund Management Office Survey Questionnaire for Existing ICT Infrastructure Inventory (2014) was used. This paper defines how Wireless Distribution System (WDS) was configured to deploy an intranet in ASIST Lagangilang Campus, Lagangilang, Abra, Philippines. Several simulation processes on network test were performed to validate the connectivity. Testing provided an understanding and confidence before deployment. Wireless Distribution System is effective in sharing Internet connectivity where physical connectivity is impossible. The use of the Digitized School map has helped a lot in providing a clear view on the vegetation in the vicinity in between buildings. Moreover, it provided assistance in decision making to which type of 802.11 wireless is appropriate in distributing the internet signal over long distances. Finally, Squid proxy server is effective in restricting accessible websites.